Effect of short term storage on wheat quality parameters - Gyimes Ernő; Csercsics Dóra; Magyar Zoltán (University of Szeged, Faculty of Engineering Szeged, 2020)
Eleven samples of registered wheat varieties of bread with diverse technological qualities were used in this study. The samples were devided into two groups. The first group including all the 11 variety were stored for 3 months, while the second group of the samples were stored for 9 months at an ambient temperature. The results of quality evaluation showed that 5 soft wheat varieties (GK Csongrád, GK Garaboly, GK Hattyú, GK Holló, GK Nap) and 6 hard wheat varieties (GK Ati, GK Békés, GK Élet, GK Kalász, GK Petúr, GK Verecke) were involved in the study. Further, the flour yield, the gluten index and the water absorbance capacity has significantly decreased after 9 months storage time when compared to 3 months storage interval.
Keywords: Mezőgazdaság-tudományok; Mezőgazdaság, erdészet, halászat